Selection of a high yielding soybean variety: Binasoybean-1 - Malek, Mohammad Abdul; Rahman, L.; Yusop, Mohd Rafii; Puteh, Adam (Gaurav Society of Agricultural Research Information Centre, 2013)
Collected 201 soybean [Glycine max (L.) Merrill] germplasm were evaluated for selection of desirable germplasm for registration as variety and/or for future utilization as breeding materials. Among the germplasm, nine were selected on the basis of better field performance considering their seed yield, morphological characters and yield attributes. Results showed that BAU-S/80 produced higher number of pods/plant and its yield was 2516 kg/ha as against 2142 and 2108 kg/ha of the two control varieties, Sohag and BARISoybean-5, respectively. Yield trials of BAU-S/80 were carried out in both rabi and kharif seasons during the period from 2007 to 2010 in selected locations under soybean growing areas of Bangladesh and found to be suitable for cultivation in the farmers' field. BAU-S/80 was found to be moderately resistant to soybean yellow mosaic virus and collar rot diseases, and also showed lower insect infestation than control varieties. On the basis of superior performance of BAU-S/80, Bangladesh Institute of Nuclear Agriculture (BINA) applied for registration to the National Seed Board NSB of Bangladesh. Consequently, the NSB of Bangladesh registered BAU-S/80 as Binasoybean-1 in 2011 for commercial cultivation in Bangladesh.